Increasing community empowerment through the promotion of halal lifestyle and the critical point of halal food in the young generation - Juni Ekowati; Alief Putriana Rahman; Hanifah Ridha Rabbani; Ghinalya Chalbi Ananda; Adinda Adelia Wulandari; Kholidah Febriani; Itsna Nur ‘Ainul Yaqin; Tiara Puspa Asriningrum; Kholis Amalia Nofianti; Noor Erma Nasution; Sugijanto Kartosentono (Journal of halal product and research (JPHR), 2020)
The halal aspect is an important factor that must be considered by Muslims in choosing food. However, the low awareness and knowledge related to halal rules and thoyyib on food had caused various serious problems. To overcome this, several government regulations have been issued, but some people still find it difficult to understand the concept of halal products. In this regard, the Faculty of Pharmacy, Airlangga University through community service conducted socialization in two schools in Rungkut Surabaya district to increase community empowerment about halal lifestyle and the critical point of food prohibition at the young generation. The method used is an online pre-test to determine the initial understanding of the participants, education in the form of counseling and discussion, and evaluation of increased understanding through pre and post-test. As partners are students, teachers, and canteen managers in Madrasah Aliyah and Madrasah Tsanawiyah school grade. Based on the analysis conducted, the results show a strong correlation between halal certification, halal awareness, and halal composition. Socialization can increase the knowledge of students and employees in those schools about the halal lifestyle and the critical point of food prohibition. Halal certification on food products affects buying interest but halal awareness and knowledge about the composition of halal food is still low in its influence on buying interest